044 Safety and efficacy of dimethyl fumarate in ESTEEM UK cohort. Issue 6 (27th May 2022) - Ford, Helen L; Su, Ray; Parks, Becky; Syndercombe, Fiona; Jones, Cynthia J
Abstract : Introduction: ESTEEM (NCT02047097 ) is an ongoing 5-year, global study characterizing long-term safety and effectiveness of routinely prescribed dimethyl fumarate (DMF) in multiple sclerosis (MS) patients. We report results from an analysis of the UK cohort of ESTEEM. Methods: The primary objective of ESTEEM is to assess the incidence, type, and patterns of serious adverse events (SAEs), and AEs leading to discontinuation of DMF in routine practice. Secondary objectives include assessment of annualized relapse rate (ARR) and proportion of patients without relapse at 6 and 12 months. Results: Of 238 UK patients (median age 42 years, 187[79%] female), SAEs were reported in 14(6%) patients. AEs leading to discontinuation occurred in n=53(22.3%) patients; the most common of these were gas- trointestinal disorders (n=20;8.4%). Unadjusted ARR declined by 84%(95%confidence interval [CI]=68– 100%; P <0.0001), from 0.74(95%CI=0.63–0.85) 12 months before enrollment to 0.12(95%CI=0.07–0.16) the year after enrollment. The proportion of relapse-free patients was 93.8%(n=223) and 87.9%(n=209) at 6 and 12 months, respectively. Conclusions: No new safety signals were observed in patients treated with DMF routinely for one year. ARR was significantly reduced vs the year prior to enrollment. Safety/efficacy results were similar between the UK and overall ESTEEM populations. Support: Biogen; disclosures detailed on poster. fiona.syndercombe@biogen.com